The effect of graphical user interface quality of management information systems on employees motivation in Islamic University in Gaza - Abu Aisha, Mahmoud Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims at identifying the impact of the quality of the graphic user-interface of management information systems on employees’ motivation to use management information system at Islamic University of Gaza, and to achieve the objectives of the study, the descriptive analytical approach was followed, and the tool of the study is a questionnaire that was distributed over a stratified random sample consists of (275) employees of academics and administratives. The study reached a number of findings, the most important of which are: In general, the effect of the quality of the graphic user interface for management information systems on employee motivation, gets overall average (3.71 out of 5), that is, with a (high) effect, and at the level of the eight domains, the most impactful was the information display page of the graphic user interface with an average of (3.94), then system messages for the user interface with an average of (3.9), and thirdly, the employee’s interaction framework with the management information system with an average of (3.84), and fourthly, the user interface work environment with an average of (3.78), and the fifth is the user interface colors with an average of (3.76), and the sixth is the visual components of the interface with an average of (3.74), and the seventh is the aesthetic environment with an average of (3.45), each dimension of previous seven dimensions has a (high) effect, and finally, user interface assistance with an average of (3.29), and an impact degree (medium). The results also showed a positive relationship (0.88), which reflects a strong relationship with a statistical significance on the level of (α<=0.05) between the quality of graphic user interface with its eight dimensions and the employees’ motivation to use management information system. The findings also reveal that there are no statistically significant differences at the level of (α<=0.05) between perceptions of respondents concerning the effect of graphic user interface quality on employees’ motivation to use the management information system attributed to the demographic variables (sex, age, qualification, field of work, years of service). According to the results, the researcher recommends providing the employee the ability to customize the graphic interface, the necessity to enhance the quality of help and beauty that the graphic interface provides, giving employees the chance to participate in designing graphic interface, innovating more facilities, and making periodic evaluation for the graphic interface usage feasibility.